Production of Valuables Organic Acids from Organic Wastes with Hydrothermal Treatment Process - Faisal, Muhammad (Jurnal Rekayasa Kimia & Lingkungan, 2009)
This article reports production of valuables organic acids from the hydrothermal treatment of representative organic wastes and compounds (i. e. domestic sludge, proteinaceous, cellulosic and plastic wastes) with or without oxidant (H2O2). Organic acids such as acetic, formic, propionic, succinic and lactic acids were obtained in significant amounts. At 623 K (16.5 MPa), acetic acid of about 26 mg/g-dry waste fish entrails was obtained. This increased to 42 mg/g dry waste fish entrails in the presence of H2O2. Experiments on glucose to represent cellulosic wastes were also carried out, getting acetic acid of about 29 mg/g-glucose. The study was extended to terephthalic acid and glyceraldehyde, reaction intermediates of hydrothermal treatment of PET plastic wastes and glucose, respectively. Studies on temperature dependence of formation of organic acids showed thermal stability of acetic acid, whereas, formic acid decomposed readily under hydrothermal conditions. In general, results demonstrated that the presence of oxidants favored formation of organic acids with acetic acid being the major product. Keywords: hydrothermal treatment, organic acids, organic wastes, oxidant, supercritical water oxidation